Animal pathogens and their impact on animal health, the economy, food security, food safety and public health - McElwain, T.F. (Rev Sci Tech, 2017)
Animal pathogens attract attention in both the livestock and public health sectors for their impacts on socio-economics, food safety and security, and human health. These impacts are felt at the household, national, regional and global levels. Whereas the World Organisation for Animal Health (OIE) has identified 118 animal diseases as notifiable, based on their potential for impact on trade, there is a selected subset that have been classified as posing a greater threat to countries due to unique characteristics, such as being highly transmissible, spreading rapidly within and between countries, and requiring cooperation between several countries to control their spread or exclude them. While these ‘transboundary diseases’ are endemic in much of the world, particularly the developing nations, many countries are classified as disease free. Following the terrorist events of 11 September 2001 in the United States, a small group of zoonotic pathogens and a group of animal-specific pathogens (those that cause what are referred to as `high-consequence foreign animal diseases’), were classified as high-risk, biothreat ‘select agents’. Rather than providing a comprehensive review of all animal pathogens, the authors briefly review the impact of these high-risk biothreat agents on animal health, the economy, food security and safety, and public health, using highly pathogenic avian influenza, foot and mouth disease and brucellosis as examples. They focus on the impact of these diseases in the context of high-income countries and low- and middle-income countries, comparing and contrasting their impact at the national and individual household levels.